Type and amount of organic amendments affect enhanced biogenic methane production from coal and microbial community structure. (1st January 2018) - Davis, Katherine J.; Lu, Shipeng; Barnhart, Elliott P.; Parker, Albert E.; Fields, Matthew W.; Gerlach, Robin
Highlights: Coal is an important carbon substrate in biogenic CBM production. Organic amendments enhance biogenic coal-to-methane conversion. Increasing amendment concentrations may not increase CH4 production proportionally. Amendment type and concentration may influence microbial community composition. Abstract: Slow rates of coal-to-methane conversion limit biogenic methane production from coalbeds. This study demonstrates that rates of coal-to-methane conversion can be increased by the addition of small amounts of organic amendments. Algae, cyanobacteria, yeast cells, and granulated yeast extract were tested at two concentrations (0.1 and 0.5 g/L), and similar increases in total methane produced and methane production rates were observed for all amendments at a given concentration. In 0.1 g/L amended systems, the amount of carbon converted to methane minus the amount produced in coal only systems exceeded the amount of carbon added in the form of amendment, suggesting enhanced coal-to-methane conversion through amendment addition. The amount of methane produced in the 0.5 g/L amended systems did not exceed the amount of carbon added. While the archaeal communities did not vary significantly, the bacterial populations appeared to be strongly influenced by the presence of coal when 0.1 g/L of amendment was added; at an amendment concentration of 0.5 g/L the bacterial community composition appeared to be affected most strongly by the amendment type. Overall, the results suggest that small amounts of amendment are not only sufficient but possibly advantageous if faster in situ coal-to-methane production is to be promoted.